Effect of Chlorhexidine on Immediate and Delayed Bond Strength between Resin and Dentin of Primary Teeth: A Systematic Review and Meta-Analysis - Masoumeh Ebrahimi; Sara Majidinia; alireza sarraf (Tehran University of Medical Sciences, 2022)
Objectives: The purpose of this study was to systematically review the literature and use meta-analysis to investigate whether chlorhexidine (CHX) application after acid etching as an adjunct treatment has any influence on the immediate and delayed bond strength to primary dentin. Materials and Methods: In this review, PubMed, ISI (all data bases), Scopus and Cochrane were searched according to the selected keywords up to April 30, 2018. The full texts of all published articles that met our primary inclusion criteria were obtained. The studies were analyzed in two parts: in vitro studies that evaluated the effect of CHX application during the bonding procedures (application after acid etching) on immediate and delay dentin bond strength of resin-dentin interface. Results: The initial search yielded 214 publications, of which 8 were selected after thorough methodological assessment. None of the clinical studies fulfilled the eligibility criteria. Our results indicated that in comparison to the control group, CHX significantly reduced immediate resin-dentin bond strength (P=0.043). These values were increased after aging (P<0.001). Conclusion: Based on this invitro Meta-analysis CHX application, improve resin-dentin bond strength durability in primary teeth.